THE IMPACT OF EXTENDED MOBILE-ASSISTED LANGUAGE LEARNING USING DUOLINGO AND WHATSAPP ON EFL SPEAKING ACCURACY AND FLUENCY: A COMPARISON ACROSS ADOLESCENT AND ADULT LEARNERS - Agus Mulyadi; Slamet Asari (University of Kuningan, 2026)
This study explores the impact of extended Mobile-Assisted Language Learning (MALL) instruction using Duolingo and WhatsApp on EFL learners’ speaking accuracy and fluency across diverse age groups. While existing studies have explored MALL in language learning, there is a gap in research on its impact on speaking accuracy and fluency, especially with the use of Duolingo and WhatsApp across different age groups. The purpose of this study is to evaluate the effectiveness of extended MALL instruction in improving EFL learners’ speaking skills, with a focus on accuracy and fluency. A quasi-experimental mixed-methods design was used, with 40 participants divided into an experimental group and a control group. Quantitative data were collected through pre-test and post-test speaking assessments, while qualitative data were gathered through questionnaires and semi-structured interviews. Data were analyzed using SPSS, including descriptive statistics, paired sample t-tests, independent sample t-tests, and effect size analysis. The results showed that the experimental group experienced statistically significant improvement in both speaking accuracy and fluency (p < 0.001), with large effect sizes (d = 1.85 for accuracy and d = 1.72 for fluency), whereas the control group showed no statistically significant improvement (p > 0.05). Significant differences were found between the two groups, confirming the effectiveness of the MALL intervention. Additionally, adolescents showed greater improvements in fluency, while adult learners demonstrated stronger improvements in accuracy. The study concludes that extended and integrated MALL instruction using Duolingo and WhatsApp provides a balanced and effective approach to developing speaking skills in EFL contexts. It highlights the importance of combining structured and communicative tools for optimal language learning outcomes.